2019
DOI: 10.1371/journal.pone.0218343
|View full text |Cite
|
Sign up to set email alerts
|

Circadian rhythms in insecticide susceptibility, metabolic enzyme activity, and gene expression in Cimex lectularius (Hemiptera: Cimicidae)

Abstract: Many insect species display daily variation of sensitivity to insecticides when they are exposed to the same concentration at different times during the day. To date, this has not been investigated in bed bugs. To address this, we explored circadian rhythms in insecticide susceptibility, xenobiotic metabolizing (XM) gene expressions, and metabolic detoxification in the common bed bug, Cimex lectularius . An insecticide susceptible Monheim strain of C . … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…The circadian rhythms of certain insects make them more susceptible to insecticides at certain times of the day than at other times [35], because the susceptibility to insecticide can be influenced by the rhythmic activity of xenobiotic metabolizing (XM) enzymes. For example, the enzymatic assay of glutathione S-transferase (GST), esterase and P450 in Cimex lectularius reveal significant time-of-day specific changes that have similar peak phases with the highest activity consistently recorded during the late photophase at ZT9 in LD [36]. The XM gene expression assays also reveal significant time-of-day differences in mRNA expression patterns in both LD and DD.…”
Section: Discussionmentioning
confidence: 99%
“…The circadian rhythms of certain insects make them more susceptible to insecticides at certain times of the day than at other times [35], because the susceptibility to insecticide can be influenced by the rhythmic activity of xenobiotic metabolizing (XM) enzymes. For example, the enzymatic assay of glutathione S-transferase (GST), esterase and P450 in Cimex lectularius reveal significant time-of-day specific changes that have similar peak phases with the highest activity consistently recorded during the late photophase at ZT9 in LD [36]. The XM gene expression assays also reveal significant time-of-day differences in mRNA expression patterns in both LD and DD.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of Anopheles gambiae , the GST activity of Pimperena strain mosquito lysates had peak phases at late-night to dawn, whereas in insecticide assays using the Mali strain, the mosquitoes showed rhythmic susceptibility to DDT with a peak at late afternoon 18 . In exploring the daily rhythms of insecticide susceptibility in the bedbug, Cimex lectularius , Khalid et al reported that the nocturnally active larvae repeatedly showed highest tolerance for deltamethrin during the late photophase at ZT9 48 . Other insects such as spotted wing Drosophila , cotton aphid, and brown plant hopper 49 51 are also reported to show circadian fluctuations in their detoxification metabolism and insecticide susceptibility.…”
Section: Discussionmentioning
confidence: 99%
“…Bed bug samples were subjected to esterase, glutathione S‐transferase (GST) and P450 activity assays following methods described by Khalid et al ., 37 with modifications. The bed bug sample was homogenized completely in 600 μl of ice‐cold 0.1 m phosphate buffer (pH 7.0) containing 0.3% Triton X‐100 (v/v) using a micro‐pestle.…”
Section: Methodsmentioning
confidence: 99%
“…Blank samples without homogenate were also included in every run as a negative control. Determination of general esterase activity and the GST assay were done according to procedures described in Khalid et al ., 37 whereas P450s assay was determined according to Son‐un et al 39 . with modifications.…”
Section: Methodsmentioning
confidence: 99%